The Effectiveness of Multimedia and Educational Games on Children’s Knowledge and Attitudes Toward Diabetes Mellitus - Mercy Nafratilova; Andra Saferi Wijaya; Rahma Annisa (Jurnal Ners, 2026)
The incidence of Diabetes Mellitus (DM) in children has increased substantially, reaching nearly seventy times compared to reports in 2010. This trend is associated with high consumption of sugary foods and beverages, rising rates of overweight and obesity, and unhealthy lifestyle patterns among children. However, more than half of children demonstrate limited knowledge regarding DM, its risk factors, and preventive strategies. This study aimed to examine the effectiveness of a Diabetes Mellitus health education intervention using multimedia and educational games on elementary school children’s knowledge and attitudes toward DM. A quantitative pre-experimental one-group pretest–posttest design was applied. A total of 127 elementary school children were selected using purposive sampling. Knowledge and attitudes were measured before and after the intervention. The results showed an increase in the mean knowledge score from 67.87 at pretest to 78.43 at posttest, while the mean attitude score improved from 33.13 to 34.96. The Wilcoxon signed-rank test indicated a statistically significant difference in knowledge scores before and after the intervention (p < 0.05). These findings demonstrate that multimedia- and educational game–based health education effectively improves children’s knowledge and attitudes toward Diabetes Mellitus